Relationship Between E-Commerce Website and Product Quality Over Customer Satisfaction - Kiki Kiki; Tantri Yanuar Rahmat Syah; Rina Anindita (Penerbit Kemala Indonesia, 2020)
This study aimed to analyse the effect of E-commerce website and product quality to customer satisfaction. In this study, the analysis was done partially to see the effect of E-commerce website to customer satisfaction also product quality over customer satisfaction and simultaneously analyse e-commerce website with product quality to customer satisfaction. This study we use analysis Structural Equation Modelling (SEM) methods to analyse customer satisfaction. Here, the data observation was collected by questionnaire with 124 respondents in e-commerce website. The sampling technique was used based on willingness to be correspondent. From the analysis results, we obtain a significant influence between the variables simultaneously website between E-commerce and product quality to customer satisfaction. Partially have a positive and significant influence between the variables of E-commerce website to customer satisfaction. The variable quality of the product is partially positive and significant impact on customer satisfaction. Increased E-commerce website services and product quality must be continued and intensified by the provider to give satisfaction to the consumer.